Implementasi Google For Education (GAFE) pada SDIT Al-Ittihad Rumbai untuk Optimalisasi Pembelajaran Daring - Lestari, Indah; Shumaya Resty Ramadhani; Ridha, Muhammad Arif Fadhly; Listiyanti, Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Several external factors such as the occurrence of disasters and the COVID-19 pandemic have limited learning activities in schools so that they must be carried out online. Teachers need to socialize how to use technology for online learning classes and schools must provide support for that. Therefore, in this community service, "Implementation of GAFE at SDIT AL-ITTIHAD Rumbai for Optimizing Online Learning". GAFE applications that will be taught include: Google meeting, classroom, gsheet, gdocs, gslides, calendar. This application was chosen because it is free for educational institutions. In addition, partners in PkM, namely SDIT AL-ITTIHAD Rumbai School, were also assisted in managing the implementation of free GAFE from Google. The coordination of these activities resulted in 4 types of outputs, namely: application of appropriate technology in the form of a school profile website, implementation of GAFE, teaching materials and workshops. From the implementation of this technology, we get a school profile website with 4 main menus with domain.sch.id, Google's approval to provide GAFE facilities to schools so that the entire community can take advantage of free GAFE facilities, teaching materials contain GAFE technology tutorials that teachers can use to learn how The use of this technology has previously been guided through workshop activities. From the workshop activities to 34 participants, consisting of the Principal, Curriculum Section and teachers, feedback was obtained 89.3% of participants felt that the material taught was very appropriate to their needs, 85.7% of participants said that this program provided benefits for solving online learning problems faced, and 75% of the participants thought that the delivery of the material was clear, interesting and easy to understand so that the goal for a more optimal implementation of online learning could be achieved.